Investigation and genotypic study on the infection of wild mouse Blastocystis sp. in Guangdong and Chongqing - Jun Xiong; Mei-Ling Cao; Xi-Long Yi; Hui-Mei Wang (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2024)
ABSTRACT Blastocystis are common digestive tract parasites in humans and animals, extensively parasitic in humans and other primates. They exhibit extensive genetic diversity; Currently, 17 subtypes (STs) and some populations called non mammalian and avian STs (NMASTs) have been proposed. To understand the infection status and genotype distribution of Blastocystis sp. in wild mouse, this study used PCR technology to study the fecal DNA samples of 111 Leopoldomys edwardsi and 117 Berylmys bowersi collected from Guangdong and Chongqing. Among 228 fecal samples, 4 samples were positive for Blastocystis sp., with a total infection rate of 1.8% (4/228). Four positive samples formed two subtypes of ST3 and ST4, all of which were zoonotic genotypes. This article aims to investigate the infection status and genotype distribution of wild mouse Blastocystis sp., which will help reduce the infection of this pathogen to animals and thereby reduce their risk of zoonotic transmission.